Breakfast consumption and the risk of depressive symptoms: The Furukawa Nutrition and Health Study. (March 2019) - Miki, Takako; Eguchi, Masafumi; Kuwahara, Keisuke; Kochi, Takeshi; Akter, Shamima; Kashino, Ikuko; Hu, Huanhuan; Kurotani, Kayo; Kabe, Isamu; Kawakami, Norito; Nanri, Akiko; Mizoue, Tetsuya
Highlights: We prospectively studied the association of breakfast with depressive symptoms. We found skipping breakfast is related to a higher risk of depressive symptoms. The associations remained after controlling for dietary and lifestyle factors. Abstract: Breakfast consumption has been suggested to influence mood, but prospective evidence on this issue is limited. We prospectively investigated the association between the frequency of breakfast consumption and the risk of depressive symptoms in Japanese employees. Participants were 716 employees aged 19–68 years who were free from depressive symptoms and mental disorders at baseline and who attended the 3-year follow-up survey. Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale. The frequency of breakfast consumption was categorized into "daily", "5–6 times/week", "3–4 times/week", "1–2 times/week", or "≤1 times/week". Logistic regression was used to estimate odds ratios of depressive symptoms according to breakfast consumption adjusted for dietary and lifestyle factors. Participants who consumed breakfast ≤1 times/week had an increased risk of depressive symptoms compared to those who ate breakfast every day, even after adjusting for other dietary factors (multivariable-adjusted odds ratio 2.92; 95% confidence interval, 1.37–6.22) The risk of depressive symptoms tended to increase with decreasing frequency of breakfast consumption (P for trend = 0.02). The omission of breakfast is related to increased risk of depressive symptoms among Japanese employees, independently of other dietary and non-dietary factors.